Life After Death: Rediscovering Life After the Loss of a Loved One - Cooke, Tony (Thomas Nelson, Inc., 1982)
In Life After Death, You will find comfort and solace for a grieving heart. You will also discover solutions for surviving the death of a loved one, as the author: Explains the gradual stages of grief recovery; Discusses ways to deal with guilt, shock, and anger; Answers tough questions about God's role in and perspective on death ...
Keywords: Bereavement; Non-Fiction